Analisa Mengenai Kependidikan pada MAS PAB 1 Sampali - Ujung, Nursholihat; Addilla, Addilla; Pasaribu, Ariyani; Nasution, Fauziah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
MAS PAB 1 Sampali is located at Jalan Pasar Hitam No. 69 Sampali, Sampali Village, Sampali Village, Percut SEI Tuan sub-district, Sampali Village, Deli Serdang district, North Sumatra Province. MAS PAB Sampali is a private school, this school is incorporated in one area or one entrance gate with several schools, so the PAB Educational Institution organizes formal education. MAS PAB 1 SAMPALI School is an educational facility located at JL. Black Market No. 69 Sampali, Sampali Village, Percut SEI Tuan sub-district, Sampali Sub-district, Deli Serdang district, North Sumatra Province was established and operational in 1988 and is still operating today. Apart from being a place of education, this school also has educators and administrators as well as school administrators with the best quality and competence in their fields, learning support activities such as extracurriculars, student organizations, learning communities, sports teams, and libraries so that students can learn optimally. MAS PAB 1 SAMPALI also guides students to have good morals (noble character), and is also a place to hone talents in various fields such as: sports in the arts and also other extracurricular activities such as Osis, Scouts and Paskibra. The facilities at the Madrasah MAS PAB 1 Sampali school can also be said to be adequate, even though the BK room is still attached to the principal's room, administration room, and UKS but there is already a special room for BK, if there are students who experience problems, they need guidance, or if you need counseling, you can go to the counseling room, the counseling room there is not too big, and there is a bathroom in it. Keywords: Madrasah, Education, Students.